Design of two-photon absorbing fluorophores for FRET antenna-core oxygen probes. (22nd February 2018) - Zheng, Zheng; Ayhan, Mehmet Menaf; Liao, Yuan-Yuan; Calin, Nathalie; Bucher, Christophe; Andraud, Chantal; Bretonnière, Yann
Abstract : Four two-photon absorbing fluorophoresA1–A4 are reported and their spectroscopic properties are analyzed for use, in combination with palladium–porphyrinato complexesC1 andC2, as two-photon absorbing antennas and energy donors for FRET-based antenna-core oxygen sensitive phosphorescent probes. Abstract : Four two-photon absorbing fluorophoresA1–A4 are reported and their spectroscopic properties are analyzed for use, in combination with palladium–porphyrinato complexesC1 andC2, as two-photon absorbing antennas and energy donors for FRET-based antenna-core oxygen sensitive phosphorescent probes. The best antennaA3 displaying the highest biphotonic brightness Φ × σ TPA = 210 GM at 800 nm was then directly grafted to the phosphorescent Pd–porphyrin cores via click chemistry to give new two-photon oxygen sensitive phosphorescent probesP1 andP2, in which energy transfer from the antenna to the core was demonstrated following two-photon excitation.